<u>First Solution</u>
-2x + y = 1
-2x + 2x + y = 1 + 2x
y = 1 + 2x
<u>Second Solution</u>
-2x + y = 1
-2x + y - y = 1 - y
<u>-2x</u> = <u>1 - y</u>
-2 -2
x = -0.5 + 0.5y
0.5 + x - x = -0.5 + 0.5 - x + 0.5y
0.5 = -x + 0.5y
-0.5y - 0.5 = -x + 0.5y - 0.5y - 0.5
2 · (-0.5y) = 2(-x - 0.5)
y = -2x - 1
<u>Third Solution</u>
-2x + y = 1
-2x + y - 1 = 1 - 1
-2x + y - 1 = 0
-2x + 2x + y - 1 = 2x
y - 1 = 2x
y - 1 + 1 = 2x + 1
y = 2x + 1
Answer:
-3/7
Step-by-step explanation:
Negative reciprocal means to put a negative and sign and change the numerator and denominator to be in opposite places.
7/3 -> -3/7
Best of Luck!